(untitled) (Qualitative Research Journal for Social Studies, 2026)
This research investigates the role of non-verbal digital communication, specifically customized stickers on WhatsApp, in shaping social interactions. With advancements in communication technology, non-verbal elements like emoji and stickers have become pivotal in text-based interactions, replacing for the lack of traditional cues such as facial expressions or vocal tones. The research focuses on university students in Lahore, Pakistan, to understand the role of stickers in emotional expression, cultural identity, and WhatsApp group dynamics. This study employs qualitative research methods, data was collected through focus groups, analyzed using thematic analysis via NVivo software. Findings reveal that stickers enrich communication by adding emotional depth and cultural relevance but also pose challenges such as misinterpretation and ethical misuse. The study contributes to the literature on digital communication and suggests the evolving role of personalized stickers in enhancing interactions.